Nesting preferences of the green sea turtle (Chelonia mydas L.) and the hawksbill sea turtle (Eretmochelys imbricata L.) in the SW of Mahe Island in the Seychelles - Mata, Fernando (2022)
Nesting preferences of the green sea turtle (Chelonia mydas L.) and the hawksbill sea turtle (Eretmochelys imbricata L.) in the SW of Mahe Island in the Seychelles. Data concerning 212 turtles emerging on the southwest beaches of Mahe Island in the Seychelles were collected in 2017 and 2018. These data were used to model the probability of eggs being laid in relation to several variables. The probability of successful laying after emergence was highest on certain beaches and in areas of short vegetation, between open sand and trees. We found successful laying was related to the physical properties of the soil, indicating that survivability of embryos and hatchlings is higher in certain areas. The turtles appeared to choose zones where soil had low salinity, good drainage but ability to retain water, and absence of spring tides and extreme temperatures.